Enhancing Laboratory Efficiency: A Community Service Program for Centrifuge Maintenance at Randegansari Husada Hospital - Setioningsih, Endang Dian; Sumber; Setiawan, Singgih Yudha; Lusiana (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
The community service program conducted by Poltekkes Kemenkes Surabaya aimed to address the problems associated with equipment maintenance at the Randegansari Husada Hospital, focusing on its centrifuge equipment in the laboratory. The program included counseling and provided practical assistance to the hospital staff, preparing them with the knowledge and skills for the proper maintenance of equipment. Activities covered recording the specification data of the centrifuge units, damage detection, performance improvement using a preventive maintenance program, and performance testing using a digital tachometer. The calibration process also proved a centrifuge relative error of 1.37% at 3000 RPM within the acceptable error limit of 10%. Verification in time, at 300 seconds, resulted in a relative error of 4.89%, also within acceptable limits. Such efforts go a step further to ensure that the centrifuge works well in contributing toward better diagnostic accuracies. The program took a portion of this staffing challenge when it embarked on the training of a medical laboratory technician, insisting that improved and sustained equipment reliability meant improved health service delivery. These would then increase at the hospital to limit malfunctioning of equipment for overall quality care